Identification of mulberry leaf flavonoids and evaluating their protective effects on H2O2-induced oxidative damage in equine skeletal muscle satellite cells - Zhang, Xinzhuang; Geng, Aopan; Cao, Di; Dugarjaviin, Manglai (Frontiers in Molecular Biosciences, 2024)
Horses are susceptible to oxidative stress during strenuous endurance exercise, leading to muscle fatigue and damage. Mulberry leaf flavonoids (MLFs) possess significant antioxidant properties. However, the antioxidant efficacy of MLFs can be influenced by the extraction process, and their impact on H2O2-induced oxidative stress in equine skeletal muscle satellite cells (ESMCs) remains unexplored. Our study employed three extraction methods to obtain MLFs: ultrasound-assisted extraction (CEP), purification with AB-8 macroporous resin (RP), and n-butanol extraction (NB-EP). We assessed the protective effects of these MLFs on H2O2-induced oxidative stress in ESMCs and analyzed the MLF components using metabolomics. The results revealed that pre-treatment with MLFs dose-dependently protected ESMCs against H2O2-induced oxidative stress. The most effective concentrations were 0.8 mg/mL of CEP, 0.6 mg/mL of RP, and 0.6 mg/mL of NB-EP, significantly enhancing EMSC viability (P < 0.05). These optimized MLF concentrations promoted the GSH-Px, SOD and T-AOC activities (P < 0.05), while reducing MDA production (P < 0.05) in H2O2-induced ESMCs. Furthermore, these MLFs enhanced the gene expression, including Nrf2 and its downstream regulatory genes (TrxR1, GPX1, GPX3, SOD1, and SOD2) (P < 0.05). In terms of mitochondrial function, ESMCs pre-treated with MLFs exhibited higher basal respiration, spare respiratory capacity, maximal respiration, ATP-linked respiration compared to H2O2-induced ESMCs (P < 0.05). Additionally, MLFs enhanced cellular basal glycolysis, glycolytic reserve, and maximal glycolytic capacity (P < 0.05). Metabolomics analysis results revealed significant differences in mulberrin, kaempferol 3-O-glucoside [X-Mal], neohesperidin, dihydrokaempferol, and isobavachalcone among the three extraction processes (P < 0.05). Our study revealed that MLFs enhance antioxidant enzyme activity, alleviate oxidative damage in ESMCs through the activation of the Nrf2 pathway, and improve mitochondrial respiration and cell energy metabolism. Additionally, we identified five potential antioxidant flavonoid compounds, suggesting their potential incorporation into the equine diet as a strategy to alleviate exercise-induced oxidative stress.